2013
DOI: 10.1371/journal.pone.0054659
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Adenocarcinoma in Malignant Pleural Effusion Enriches Cancer Stem Cell Properties during Metastatic Cascade

Abstract: BackgroundMetastasis occurs in a series of discrete steps involving invasion, angiogenesis, lymphovascular space permeation, and establishment of secondary tumors. Malignant pleural effusion (MPE), a type of tumor metastasis, is usually a poor prognostic sign for patients with pulmonary adenocarcinoma, although its underlying mechanism has received less attention than other types of metastases have. The objective of the current study was to confirm whether cancer stem cells (CSCs) in MPE contribute to the “met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
57
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 52 publications
3
57
0
Order By: Relevance
“…We found here, from clinical specimens and in vitro experiments, that cancer cells in malignant PE/ascites underwent EMT and displayed a cancer stem cells phenotype, which could account for the poor prognosis. Here, besides confirming the phenomena described previously (9,19,20), we also found that malignant exudates had universal induction activity regardless of tumor type and origin. More importantly, we noted that non-CSCs could undergo EMT process and be directly converted into the CSC state when exposed to malignant PE/ascites; therefore, blocking the process in combination with conventional chemotherapies is critical to better control malignant PE/ascites.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found here, from clinical specimens and in vitro experiments, that cancer cells in malignant PE/ascites underwent EMT and displayed a cancer stem cells phenotype, which could account for the poor prognosis. Here, besides confirming the phenomena described previously (9,19,20), we also found that malignant exudates had universal induction activity regardless of tumor type and origin. More importantly, we noted that non-CSCs could undergo EMT process and be directly converted into the CSC state when exposed to malignant PE/ascites; therefore, blocking the process in combination with conventional chemotherapies is critical to better control malignant PE/ascites.…”
Section: Discussionsupporting
confidence: 91%
“…EMT and gain a stem cell phenotype within malignant PE/ascites (9,19,20). So far, however, there are no available strategies to inhibit these processes because the underlying mechanisms are barely understood.…”
mentioning
confidence: 99%
“…In addition, no statistically significant difference was observed between the two groups in terms of the expression of Snail-1/Snail-2 and p-p38 MAPK, which are major signal transducing molecules in EMT. A previous study provides one possible explanation for the reduced expression of NANOG observed in PSC: Chen et al (36) assessed the expression of NANOG in primary tumours at the frontline between tumour and normal tissue, and in malignant pleural effusions of PA, demonstrating that a situation-dependent up-regulation of the NANOG gene occurred at the frontline of tumour progression compared with quiescent areas. According to the hypothesis of Chen et al (36), quiescent tumour cells obtained from PSC may express only small amounts of NANOG.…”
Section: Discussionmentioning
confidence: 98%
“…Nearly 15% of newly diagnosed lung cancer patients have pleural effusion, and 40–50% of lung cancer patients will have pleural effusion during disease progression. Malignant pleural effusion has a complex composition, containing a small number of tumor cells and cancer stem cells (CSCs) . In pleural effusions, lymphocytes account for 50–70% of all nucleated cells.…”
Section: Introductionmentioning
confidence: 99%